Laparoscopic partial pancreatectomy through an advanced lateral approach as treatment for insulinoma in dogs: a case series - Keulen, Justin N. P.; van Nimwegen, Sebastiaan A. (Frontiers in Veterinary Science, 2024)
A minimally invasive partial pancreatectomy was performed through a novel laparoscopic lateral flank approach in sternal-oblique recumbency in 4 clinical cases presented with an insulinoma. All 4 cases were female castrated dogs of older age (range 7-9 years) and different breeds (Wire haired dachshund, German shepherd, Jack Russel terrier, and Boxer), and all presented with episodic weakness, tremors, and/or seizures.Diagnosis was based on plasma glucose level below reference range with concomitant increased or normal insulin level. A laparoscopic approach was considered based on triple-phase contrast-enhanced computed tomography findings of the abdomen, revealing a pancreatic mass situated in the right-or left pancreatic limb without suspicion of metastasis. Laparoscopic procedures were performed without any major complications and peri-operative glycemia increased to (supra-)normal levels in all cases. Histopathologic reports qualified the masses as neuroendocrine carcinomas, and in conjunction with the clinical picture, these neoplasia's were further defined as insulinoma. Post-operative care in an intensive care unit was of short duration and all animals were discharged being clinically normal and normoglycemic in between 1.5-and 2.5-days postsurgery. At short-term follow-up no dogs showed clinical abnormalities, all recovered well from the surgical procedure, and blood glucose levels remained in normal range. During long-term follow-up 2 cases remained clinically normal at the time of writing, 564 and 1211 days after surgery, 1 dog had recurrence of hypoglycemic episodes after 246 days and was euthanized 673 days post-surgery due to progressing disease, and 1 dog was euthanized 1028 days after surgery due to reasons unrelated to the insulinoma. Survival times ranged from 599 to 1232 days after diagnosis. Considering the highly metastatic nature and difficulty of full laparoscopic staging of insulinoma patients, thorough pre-operative disease staging is warranted when considering a laparoscopic approach. This case-series shows the feasibility of a novel laparoscopic flank approach for right and left partial pancreatectomy in dogs. Furthermore, proper case selection resulted in favorable outcome in these insulinoma patients.